Using a Blog to Guide Beginner Students to Use Adjectives Appropriately When Writing Descriptions in English - Omar Yesid Lizarazo Jara (Universidad Nacional de Colombia, 2012)
Beginner students often have difficulties using adjectives when they write descriptions in English. This article focuses on the procedures used to help my sixth grade students understand and use adjectives in the correct order by using a blog. To achieve the objective of the project I decided to implement an innovation in and out of class practices, particularly when guiding students in writing descriptions. Hence, different activities were designed using some worksheets during the lessons in the classroom and some exercises implemented in a blog. The results showed that at the end of the implementation the majority of students' descriptions improved in terms of using adjectives related to nouns and the students increased their understanding of the use of this grammar issue.